Temporal Pattern Changes with Speed in Cross-Country Skiing - Tveit, P.; Nilsson, J.; Smith, G. (2002)
Temporal characteristics of movement patterns describe some of the most fundamental aspects of locomotion. In skiing, the various techniques are well defined patterns which are invariant across speed. This has implications for learning and training in that it allows skiers to develop the motor control patterns at relatively slow speeds and apply them in faster skiing. In addition, control of speed in skiing is primarily a function of cycle rate. To ski faster, the tempo or rate is increased. Speed and cycle rate are directly related while cycle length is nearly constant. This control mechanism is quite different from running for example where through the range of distance running speeds stride length is the primary control variable.